Colour as an Art of Illusion in John Lyly’s Campaspe (1584) - Armelle SABATIER (E-REA)
While the renowned painter Apelles praises his future sitter’s beauty in John Lyly’s Campaspe, act 3 scene 1 (1584), the young Campaspe rejects his flattering speech, hinting that the oily material harmoniously brushed onto a canvas is merely akin to the deceitful conceit of colores rhetorici. This conventional association of pictorial art with the art of rhetoric offers a glimpse of the complex discussion about colours that Lyly dramatised in his first comedy. This article aims at exploring the diverse meanings of colours in Campaspe in the light of Elizabethan perceptions of colours, focussing more particularly on the relation between colour and illusion. The dramatization of colours unveils Lyly’s fascination with artistic theories on colours as well as his deep concern with contemporary literary fashions that threaten the vitality and innovation of chromatic writing.